Optical access networks and advanced photonics technologies and deployment strategies - Chochliouros, Ioannis P., 1966-; Heliotis, George A., 1975- (Information Science Reference, 2010)
"This book presents a comprehensive overview of emerging optical access network solutions to efficiently meet the anticipated growth in bandwidth demand"--Provided by publisher.